The Meaning of the Sweet - Mangano, Dario (E|C, 2020)
In this paper we will focus on the way in which an expressive configuration correlates with a semantic configuration both with respect to a single text-object, such as a specific dessert, and with respect to a micro-universe of text-objects, such as sweets made with ricotta. The relationship that is created between the planes of a semiotic system does not in fact concern only the single elements, but also their broader universes understood as parts of a single mechanism that Lotman calls semiosphere.